A Southern Shakespeare? - Michèle Vignaux (Transatlantica)
America’s relationship to Shakespeare is notoriously ambiguous, wavering between rejection and appropriation. Among the causes of this ambivalence is the underlying tension between the democratic ideal of the United States and the association of Shakespeare with the old European feudal order, itself associated by Walt Whitman with slavery in the old South. Hence the idea to explore the North/South dichotomy in the nineteenth-century. This paper will address issues such as the extent to which the North/South geographical and cultural divide coincided with other dichotomies like that of Shakespeare on page/on stage, or whether there was a Southern specificity in terms of reception as well as of influence on literary creation, unveiling in the process secret thematic similarities.